2021
DOI: 10.1039/d1ra00367d
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the dissolution and diffusion properties of interstitial oxygen at grain boundaries in body-centered-cubic iron by the first-principles study

Abstract: Oxygen atoms prefer to segregate to grain boundaries (2/2′). They segregate to Σ3〈110〉(111) with low energy barrier, but concentrate at the transition region of Σ5〈001〉(310) due to high energy barrier. They diffuse in grain boundaries (3/3′) more than in bulk (1/1′).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 39 publications
2
6
0
Order By: Relevance
“…Moreover, the solution energies of O atoms in the near-Fe(110) surface region are generally higher than those in the near-Fe(100) surface region, indicating that O atoms dissolve in the near-Fe(110) region more hardly than in the near-Fe(100) region. The black horizontal dash line indicates the solution energy (−1.20 eV [15,16,22] ) of an interstitial O atom at octahedron position in bulk.…”
Section: The Effects Of Oxygen Coverage On Oxidation Corrosionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, the solution energies of O atoms in the near-Fe(110) surface region are generally higher than those in the near-Fe(100) surface region, indicating that O atoms dissolve in the near-Fe(110) region more hardly than in the near-Fe(100) region. The black horizontal dash line indicates the solution energy (−1.20 eV [15,16,22] ) of an interstitial O atom at octahedron position in bulk.…”
Section: The Effects Of Oxygen Coverage On Oxidation Corrosionmentioning
confidence: 99%
“…[17] However, they are easily trapped by vacancy defects and grain boundaries, which also slow down the diffusion of oxygen. [20][21][22] Besides, the effects of alloying atoms on the solution and diffusion of oxygen are also explored in Fe-based alloys. [21,23] The bond order analysis potential of the Fe-O system has been proposed to reproduce the fundamental properties of the Wustite and the energetics of oxygen atoms in α-iron.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on atomistic calculations, Shang et al investigated the diffusivity of interstitial O in bcc-Fe with and without a vacancy, and found that O in the octahedral interstice is always energetically favorable [25]. By investigating the solution and diffusion properties of O atoms at different Fe-GBs, Liu found that GBs could attract interstitial O and hinder O diffusion, and vacancies in GBs could accelerate diffusion of O atoms [26]. Additionally, the orientation of the surface and the concentration of O could also affect the adsorption of O atoms on the Fe surface and the oxidation corrosion [27].…”
Section: Introductionmentioning
confidence: 99%
“…Herein, atomistic simulations based on first-principles calculations were conducted to explore the influence of alloying elements on the solution and diffusion of O at GBs in bcc-Fe based structural materials. Based on our previous work [26], the Fe-GB of Σ5(310), having a stronger attraction of O than Σ3(111)/ [110], was chosen to explore the effects of three typical alloying elements (Si, Cr, Mo) on the solution and diffusion behaviors of O in the GB. Firstly, the segregation energies of alloying atoms near the GB were calculated to find their stable sites at the GB.…”
Section: Introductionmentioning
confidence: 99%